Sigapiton Tourism Village Development Strategy, Ajibata District, Toba Regency - Frengki Simbolon; Anwari Masatip; Sumihar Sebastiana (Universitas Katolik Widya Karya Malang, 2023)
Sigapiton Village is one of the villages designated as a tourist village in Toba Regency based on the decision of the Toba Regent Number 665 of 2020, Sigapiton Village is designated as a Tourism Village. Sigapiton Tourism Village has the potential of a tourist attraction, but has not been developed to its full potential. This study aims to identify and describe the profile of potential tourist attractions owned by Sigapiton Tourism Village, identify and analyze internal and external factors that influence the development of Sigapiton Tourism Village, and develop tourism development strategies in Selulung Tourism Village. This study uses a qualitative method with the analysis of IFE, EFE, IE. Data collection was done by observation, interviews, Focus Group Discussion, giving questionnaires, examining documents and literature studies. The tourism potential of the Sigapiton Tourism Village is the potential for natural, cultural and man-made tourist attractions. Internal factors that influence the development of the Sigapiton Tourism Village are its natural and cultural attractions, tourism facilities, human resources and commitment to building a tourist village. External factors that influence are market trends (alternative tourism), well-known tourist destinations (Situmurun waterfall), Sister Village has been established between Silima Lombu and Sigapiton Tourism Village, and support from the government. The development strategy that can be applied in the Sigapiton Tourism Village is to develop tour packages that prioritize culture, art, local traditions, and agro-tourism, create interesting content marketing and carry out promotions, and build synergy with the surrounding tourist villages in Ajibata sub-district, Kabupaten Sigapiton. Toba.